Le passif et les converses de relation - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2006)
Verbs in the passive voice along with their active counterparts have been frequently associated with couples of converse relations. The present paper disclaims, on historical and inflectional grounds, the existence of equivalence between them. Although similar, each of these types of expressions exhibits a significant number of peculiar traits. The main argument put forward states that formal differences between active and passive forms are a main hindrance to treat them analogously to converse relations.